Pengaruh Insentif Finansial dan Non Finansial terhadap Kinerja Karyawan Hotel Timeshare dengan Variabel Mediasi Kepuasan Kerja - Ni Luh Dita Priliani; Ida Ayu Putri Widawati; Irene Hanna H. Sihombing (JURNAL BISNIS HOSPITALITI, 2021)
Employee performance is seen as what an employee does and what he doesn't do. Employee performance involves the quality and quantity of output, attendance at work, and timeliness of output. The level of absenteeism is quite high where an average of 14.59% per month. This can have a negative effect on employee performance, meaning that the higher the level of absenteeism will affect the lower performance of the employee. There are indications that employee job satisfaction is not optimal due to inaccurate provision of financial and non-financial incentives. Given this phenomenon, it is interesting to study given the tendency of low employee performance, the possibility of giving inappropriate or unsatisfactory incentives which causes low job satisfaction. Data were collected using a questionnaire method to 104 respondents at Karma Royal Bali. Data were analyzed using SmartPLS software. The results are that financial incentives and non-financial incentives have a positive and significant effect on job satisfaction and job satisfaction as a mediator between financial incentives and non-financial incentives on employee performance at Karma Royal Bali.